Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1991
DOI: 10.1007/bf02244380
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the pharmacology of the pro-convulsant effects of α2-adrenoceptor antagonists in mice

Abstract: The effects of selective and specific alpha 2-adrenoceptor antagonists on electroshock seizure threshold in mice were investigated. Idazoxan, at low doses, efaroxan, RX811059 and RX821002 significantly lowered seizure threshold. The alpha 1-agonist St 587 and the beta-agonist isoprenaline were also pro-convulsant. On the other hand the alpha 2-agonists clonidine and UK 14,304 produced small increases in seizure threshold. Anticonvulsant effects were also produced by low doses of the noradrenaline uptake inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
9
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 19 publications
5
9
0
Order By: Relevance
“…We postulate that the anticonvulsant action of N E is mediated via ␣2-ARs. Indeed, agonists selective for the ␣2-ARs have been shown to exert anticonvulsant effects against audiogenic seizures in mice, as well as against PTZ-, kainic acid-, and bicuculline-induced seizures; ␣2-AR antagonists have the reverse effect (Papanicolaou et al, 1982;Baran et al, 1985;L oscher and C zuczwar, 1987;Fletcher and Forster, 1988;Jackson et al, 1991). However, it has not been determined whether the anticonvulsant effect of ␣2-AR agonists is mediated via the pre-or postsynaptic receptors.…”
Section: Without Dopssupporting
confidence: 41%
See 1 more Smart Citation
“…We postulate that the anticonvulsant action of N E is mediated via ␣2-ARs. Indeed, agonists selective for the ␣2-ARs have been shown to exert anticonvulsant effects against audiogenic seizures in mice, as well as against PTZ-, kainic acid-, and bicuculline-induced seizures; ␣2-AR antagonists have the reverse effect (Papanicolaou et al, 1982;Baran et al, 1985;L oscher and C zuczwar, 1987;Fletcher and Forster, 1988;Jackson et al, 1991). However, it has not been determined whether the anticonvulsant effect of ␣2-AR agonists is mediated via the pre-or postsynaptic receptors.…”
Section: Without Dopssupporting
confidence: 41%
“…(1) selective lesioning of noradrenergic neurons (with 6-hydroxydopamine or DSP-4) increases seizure susceptibility to a variety of convulsant stimuli (Arnold et al, 1973;Jerlicz et al, 1978;Mason and Corcoran, 1979;Snead, 1987;Trottier et al, 1988;Sullivan and Osorio, 1991;Mishra et al, 1994); (2) direct stimulation of the locus coeruleus (LC, the major concentration of noradrenergic cell bodies in the C NS) and the subsequent release of N E reduce C NS sensitivity to convulsant stimuli (Libet et al, 1977;T urski et al, 1989); (3) genetically epilepsy-prone rats (GEPRs), a widely used animal model of epilepsy, have deficient presynaptic N E content, N E turnover, tyrosine hydroxylase levels, dopamine ␤-hydroxylase (DBH) levels, and N E uptake (Jobe et al, 1984;Dailey and Jobe, 1986;Browning et al, 1989;Lauterborn and Ribak, 1989;Dailey et al, 1991); and (4) adrenergic agonists acting at the ␣-2 adrenoreceptor (␣2-AR) have anticonvulsant action (Papanicolaou et al, 1982;Baran et al, 1985;Loscher and C zuczwar, 1987;Fletcher and Forster, 1988;Jackson et al, 1991).…”
mentioning
confidence: 40%
“…Other studies have suggested either anticonvulsive or proconvulsive effects of clonidine, depending on the seizure etiology or on the dose of clonidine administered. The studies of Papanicolaou et al (16) and Jackson et al (15) indicated an anticonvulsive e k c t of low doses of clonidine, mediated most likely by a,-adrenoceptors, whereas higher doses decreased seizure thresholds in experimental animals, an effect probably mediated through a,-adrenoceptors (15,16). However, all these studies report data obtained from experimental animals.…”
Section: Discussionsupporting
confidence: 38%
“…Clonidine is routinely used as a premedication (15). Because it has an effect on the seizure threshold in experimental animals (16)(17)(18)(19), we also evaluated its effect on focal epileptiform activity.…”
mentioning
confidence: 45%